Regulation of Human Macrophage M1–M2 Polarization Balance by Hypoxia and the Triggering Receptor Expressed on Myeloid Cells-1 - Raggi, Federica; Pelassa, Simone; Pierobon, Daniele; Penco, Federica; Gattorno, Marco; Novelli, Francesco; Eva, Alessandra; Varesio, Luigi; Giovarelli, Mirella; Bosco, Maria Carla (Frontiers in Immunology, 2017)
Macrophages (Mf) are a heterogeneous population of tissue-resident professional phagocytes and a major component of the leukocyte infiltrate at sites of inflammation, infection, and tumor growth. They can undergo diverse forms of activation in response to environmental factors, polarizing into specialized functional subsets. A common hallmark of the pathologic environment is represented by hypoxia. The impact of hypoxia on human Mf polarization has not been fully established. The objective of this study was to elucidate the effects of a hypoxic environment reflecting that occurring in vivo in diseased tissues on the ability of human Mf to polarize into classically activated (proinflammatory M1) and alternatively-activated (anti-inflammatory M2) subsets. We present data showing that hypoxia hinders Mf polarization toward the M1 phenotype by decreasing the expression of T cell costimulatory molecules and chemokine homing receptors and the production of proinflammatory, Th1-priming cytokines typical of classical activation, while promoting their acquisition of phenotypic and secretory features of alternative activation. Furthermore, we identify the triggering receptor expressed on myeloid cells (TREM)-1, a member of the Ig-like immunoregulatory receptor family, as a hypoxia-inducible gene in Mf and demonstrate that its engagement by an agonist Ab reverses the M2-polarizing effect of hypoxia imparting a M1-skewed phenotype to Mf. Finally, we provide evidence that Mf infiltrating the inflamed hypoxic joints of children affected by Oligoarticular Juvenile Idiopatic Arthritis (OJIA) express high surface levels of TREM-1 associated with predominant M1 polarization and suggest the potential of this molecule in driving M1 proinflammatory reprogramming in the hypoxic synovial environment.